Maternal health tracker web application system - Sawe, Mercy Jepkoech (Strathmore University, 2021)
Excellent maternal healthcare in Kenya and the world at large is still a work in progress. The slow improvement in global maternal health has necessitated the healthcare sector to look for supplementary technological solutions. Delayed response to symptoms during antenatal care is a major cause of pregnancy related mortality in Kenya. Timely signal of abnormal symptoms during pregnancy leads to reduced risk of pregnancy-related complications in an expectant woman. This study aimed at assisting in reducing maternal mortality rate in the country, through development of a web application that analyses the daily input symptoms during pregnancy and timely signals any deviation from the normal expected symptoms. Rapid Application Development (RAD) methodology was used in building the system since the maternal health study had well-defined requirements. In addition, RAD methodology has an incremental approach that facilitated early testing of the system, and this was a determinant of whether the development was on the right track in terms of a working solution. The solution tracks pregnancy progress and issue a timely signal of any abnormal symptom and in the long run minimize the possibility of pregnancy-related complications
An information System documentation Submitted to the Faculty of School of Computing and Engineering Sciences in partial fulfillment of the requirements for the award of a Degree in Business Information Technology
Keywords: Marternal health; Application system; Tracker